BREWERS’ SPENTGRAIN: BIOACTIVITY OF PHENOLIC COMPOUNDS; APPLICABILITY IN ANIMAL NUTRITION AND FUNCTIONAL FOODS - Stefanello, Flávia Santi; Fruet, Ana Paula Burin; Simeoni, Caroline Posser; Chaves, Brunele Weber; Oliveira, Lidia Cauduro de; Nörnberg, José Laerte (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The wide availability of brewers’ spentgrain (BG) low-cost, associated with thecurrent interest in the health benefits of phenolic acids, opens new possibilities for the use. This review details the potential bioactivities of phenolic compounds present in the BG and its incorporation in animal nutrition and functional foods. The literature shows that the phenolic compound including ferulic, p-coumaric and caffeic acid can have antioxidant, anti-carcinogenic, anti-inflammatory andanti-atherogenic activities. Since these phenolic acids are some of the major phenolic in BG, it is expected that may exhibit similar properties. The BG works as an alternative for animal nutrition, with many nutritional benefits. Although some attempts have been made to incorporate the bioactive components in foods RC, more research is needed in this area.